2004
DOI: 10.1093/jee/97.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil Compaction on Tunnel Network Construction by the Eastern Subterranean Termite (Isoptera: Rhinotermitidae)

Abstract: Reliance on use of the Petri dish for bioassay studies has resulted in the majority of subterranean termite research being conducted in a manner that has not taken into account one of the most important feature of subterranean termites ecology: the soil in which they live. This artificial environment for bioassays, favored for its ease of use, may have resulted in accumulation of data about termite physiology, toxicology, pathology and behavior with limited biological relevancy. Caution should be taken when dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…The experimental design did not allow an unfettered view of the specific role of the various mouthparts in the excavation process, but the activities observed generally matched previous descriptions 17, 28–32. Termites excavated soil particles instead of squeezing between pores.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The experimental design did not allow an unfettered view of the specific role of the various mouthparts in the excavation process, but the activities observed generally matched previous descriptions 17, 28–32. Termites excavated soil particles instead of squeezing between pores.…”
Section: Discussionmentioning
confidence: 73%
“…Effects of non‐repellent compounds on the foraging range and activity of subterranean termites were studied under both laboratory and field conditions 15, 16. The influence of soil compaction,17 moisture gradients18 and the presence of sound or decayed wood on tunneling behavior and ability of termites has also been examined 19. There is still little information, however, on the effects of fipronil and indoxacarb on the tunneling behavior and walking ability of termites.…”
Section: Introductionmentioning
confidence: 99%
“…These activities are difficult by increased soil compaction. Tucker et al (2004) found that construction speed of tunnel network varied with soil compaction, being much slower in the more compacted soil (1.35 g/cm 3 ). Although this study was conducted under laboratory conditions using a different substrate and moisture content, and it cannot be directly compared with the present study, however, clearly the same relationship was observed.…”
Section: Physical Soil Variables and Relationship With Termite Speciesmentioning
confidence: 96%
“…Termites economically important pests when they started to destroy the wood and wooden products of human homes, building materials, forests, agricultural crops and other commercial products [2]. The red loamy soil influences construction of termatorium and fungal comb construction by termites [3]. The Vayalogam soil series of Pudukottai district is a red sandy loam soil covering 1.69 lakh hectares.…”
Section: Introductionmentioning
confidence: 99%